The Impact of Green Marketing on Environmentally Friendly Consumer Behavior in Restaurants in Medan City - Saut Maruli Tua Pandiangan; Josua Alexander Gultom; Pretty Luci Lumbanraja; Hotbona Novandi Tambunan; Sarah Betty Tiomsi Simamora (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
One of the main issues that is a concern for environmental damage is the decline in awareness of environmentally friendly consumer behavior, such as the lack of clear information about environmentally friendly products, higher prices for environmentally friendly products, and the lack of ease in finding and purchasing these products. The problem of declining awareness of environmentally friendly consumer behavior and several factors contributing to this decline have given rise to solutions to environmental issues through green marketing, which includes green product, green price, green place, and green promotion. This study aims to identify the characteristics of environmentally friendly consumer, analyze the impact of green marketing on environmentally friendly consumer behavior, and explore innovative strategies for implementing green marketing policies on environmentally friendly consumer behavior in Restaurants in Medan City. This study used a mixed-methods data analysis approach, incorporating qualitative and quantitative analysis, with 100 respondents representing environmentally friendly consumers in Restaurants in Medan City. Data analysis was conducted using descriptive analysis, multiple linear regression analysis, and the quadruple helix model. The results show that green product variable has a positive and significant effect on environmentally friendly consumer behavior in Restaurants in Medan City. Green price variable has a positive and significant effect on environmentally friendly consumer behavior in Restaurants in Medan City. Green place variable has a positive and significant effect on environmentally friendly consumer behavior in Restaurants in Medan City. Green promotion variable has a positive and significant effect on environmentally friendly consumer behavior in Restaurants in Medan City.